Survey on Real-world Applications and Challenges of Deep Learning-Enhanced Techniques to assist visually impaired - Rashmi B N (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This comprehensive survey report delves deeply into the real-world applications and complicated issues inherent in deep learning-enhanced wearable solutions for people with vision impairments. It stresses the global incidence of visual impairment, particularly in underserved areas, and follows the growth of assistive devices over time. The study examines deep learning's revolutionary function, demonstrating its impact through real-world case studies such as OrCam MyEye and Brain-Computer Interfaces. It does, however, rigorously identify the various technical challenges, such as data accessibility and real-time processing, as well as ethical concerns, such as privacy and fairness. In conclusion, while the paper highlights the potential of deep learning to empower people with disabilities, it also calls for the continual resolution of these obstacles to construct a more inclusive and accessible future. We need to focus on designing small size object detection and object recognition systems which consider varying size images, to address the problems faced by the visually impaired in their passive and active stages, according to the study.